FRI0612-HPR The Development of Physiotherapy-Led Musculoskeletal Triage Services in Ireland. (15th July 2016) - Brennan, A.; Breen, R.; Ashton, J.; Edel, C.; Farrell, C.; Moore, D.; Kenny, P.; FitzGerald, O.
Abstract : Background: In 2012, funding was approved for twenty-four Advanced Practice Physiotherapy (APP) posts in Ireland through the Clinical Strategy and Programmes Directorate of the HSE. These posts were to provide orthopaedic and rheumatology triage clinics across 16 hospitals throughout the country. Objectives: The aims of these clinics were to reduce the waiting time for outpatient consultation for orthopaedic and rheumatology patients; to establish a diagnosis and triage patients along the most appropriate care pathway according to their diagnosis. Methods: Initially 18 APPs were recruited in 2012 and currently there are 22.5 in post nationally. Guidelines regarding inclusion for attendance at these clinics were disseminated to APPs recruited to posts. Clinical governance for APP clinics is provided by either a consultant orthopaedic surgeon or a consultant rheumatologist who provide support with clinical diagnosis; with the ordering of investigations and with management of patients as appropriate. Results: From January 2012 to May 2015 48, 279 patients have been removed from orthopaedic and rheumatology waiting lists nationally. In orthopaedic clinics APPs reviewed 33, 092 new patients and discharged 25, 917 (78%); in rheumatology clinics APP's reviewed 7, 550 new patients and of this 5, 417 (72%) were discharged following their review. Conclusions: Advanced Practice Physiotherapist's can assist in the management of orthopaedic and rheumatology waiting lists. These services provide patients with early access for a specialist opinion and management and therefore prevent chronicity of symptoms. It can be hypothesized that prevention of chronicity would result in a reduction in the use of health care resources by this subgroup of patients. Disclosure of Interest: None declared